2021
DOI: 10.1111/njb.03242
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the taxonomy of little known Tragopogon species endemic to Turkey

Abstract: In the present paper, two little-known species (T. olympicus Boiss. and T. pichleri Boiss.) endemic to Turkey are evaluated in terms of morphology based on numerous authentic and/or new collections. Additionally, the phylogenetic positions of these little-known species are evaluated based on newly generated sequences of nrDNA ITS, trnL and trnL-F. As a result of the morphological examination, lectotypes are designated and documented for both species together with amended diagnosis. The phylogenetic analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(80 reference statements)
0
5
0
Order By: Relevance
“… Majority‐rule consensus cladogram of Tragopogon from ML analysis based on a nrDNA ITS dataset (support values: first‐line ML bootstrap and JK jackknife, second‐line pp posterior probability). Clade names are in accordance with those of Gültepe et al (2021), and Clades IV and V are indicated by a thick black bar.…”
Section: Key To Tragopogon Davutii‐turanii and Closely Related Taxa I...mentioning
confidence: 68%
See 3 more Smart Citations
“… Majority‐rule consensus cladogram of Tragopogon from ML analysis based on a nrDNA ITS dataset (support values: first‐line ML bootstrap and JK jackknife, second‐line pp posterior probability). Clade names are in accordance with those of Gültepe et al (2021), and Clades IV and V are indicated by a thick black bar.…”
Section: Key To Tragopogon Davutii‐turanii and Closely Related Taxa I...mentioning
confidence: 68%
“…Since Tragopogon is a relatively new genus with high species diversity and diversification rates, analyses based on molecular markers, including nuclear and plastid DNA, show poor resolution (Bell et al 2012, Mavrodiev et al 2012, Gültepe et al 2021). Besides, even if there is no support and most of the taxa collapse after cutting the 50 % threshold resulting in a polytomy, there are distinct clades in the tree (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Tragopogon L. (Asteraceae) contains about 150 species worldwide and widespread in semiarid and mountainous regions of Europe and Asia [1]. 26 taxa belonging to 22 species are distributed throughout Turkey [2]. It is morphologically similar to T. oligolepis Hartvig & Strid is local endemic to the Southwest of Anatolia [3].…”
Section: Introductionmentioning
confidence: 99%